Uric Acid-Induced Adipocyte Dysfunction Is Attenuated by HO-1 Upregulation: Potential Role of Antioxidant Therapy to Target Obesity - Komal Sodhi; Jordan Hilgefort; George Banks; Chelsea Gilliam; Sarah Stevens; Hayden A. Ansinelli; Morghan Getty; Nader G. Abraham; Joseph I. Shapiro; Zeid Khitan (Stem Cells International)
Increased uric acid levels have been implicated in the pathogenesis of metabolic syndrome. To examine the mechanisms by which this occurs, we hypothesized that an increase in heme oxygenase 1, a potent antioxidant gene, will decrease uric acid levels and adipocyte dysfunction via suppression of ROS and xanthine oxidase (XO) levels. We examined the effect of uric acid on adipogenesis in human mesenchymal stem cells (MSCs) in the presence and absence of cobalt protoporphyrin (CoPP), an HO-1 inducer, and tin mesoporphyrin (SnMP), an HO activity inhibitor. Uric acid increased adipogenesis by increasing NADPH oxidase expression and elevation in the adipogenesis markers C/EBPα, PPARγ, and Mest, while decreasing small lipid droplets and Wnt10b levels. We treated MSCs with fructose, a fuel source that increases uric acid levels. Our results showed that fructose increased XO expression as compared to the control and concomitant treatment with CoPP significantly decreased XO expression and uric acid levels. These beneficial effects of CoPP were reversed by SnMP, supporting a role for HO activity in mediating these effects. These findings demonstrate that increased levels of HO-1 appear crucial in modulating the phenotype of adipocytes exposed to uric acid and in downregulating XO and NADPH oxidase levels.